Análisis comparativo de las obras carta al padre y la metamorfosis de Franz Kafka - Flores Troya, Sandro Alfredo (2016)
The research paper entitled "COMPARATIVE ANALYSIS OF WORKS, LETTER TO FATHER AND Metamorphosis, Franz Kafka" general objective: List the major differences in the psychological aspect of each work. For the development of research we used various methods such as: scientific, analytical-synthetic, inductive-deductive, descriptive and specific method was comparative. The technique was applied literature, which allowed for a lot of selected to apply throughout the investigation. solidarity, responsibility, respect, obedience and negative values as: Among the results comparative analysis, thematic clarification of the two works, where nature and history of each is emphasized, involving human values stands contempt, authoritarianism, which are the fundamental part that emphasized in the content of the two works of Franz Kafka, where the author expresses his father, his feelings and desolation. From all this we conclude that each work conveys its own worldview and that similar structures of thought between the two works may be related, in addition to Franz Kafka, took each of them differentiated by their arguments, LETTER TO THE FATHER, the protagonist is a child educated with authoritarianism, in metamorphosis, it is the transformation of a person into an animal. Faced with these findings is recommended that scholars for the field of Comparative Literature at the School of Spanish Language and Literature scientifically instrumented components.